ANPEd e as produções intelectuais: um mapeamento das produções científicas a respeito da educação escolar indígena - Carmo, Isomar Portela do (Brasil, 2023)
School education is one of the main concerns linked to the indigenous struggle to guarantee their rights, which were conquered with much struggle and established in 1988 with the Federal Constitution. This education is also responsible for the process of valuing the indigenous identity, considering that it provides the transmission of values and culture in such a way that the new generations can rework their understanding of the composition of the current society. With this in mind, this research aimed to map the intellectual productions on indigenous school education in the national events of the National Association of Graduate Studies - ANPED in all its working groups in the period from 2007 to 2017, with specific focus on the analysis regarding the quantity, issues addressed, methodological processes adopted, and the institutions that developed these Works. It is observed from the data that research on indigenous school education is still incipient, throughout the research we identified a total of 34 (thirty-four) papers in 10 (ten) years.